Content Analysis of VIVA Cosmetics' Brand Identity on Instagram as a Legendary Local Brand - Grissa Gaviota Zada; Heidy Arviani (Lavish Opulent Education, 2026)
In the digital era, social media has become an essential platform for brands to communicate their identity and engage with audiences. As one of Indonesia’s long-established local cosmetic brands, Viva Cosmetics utilizes Instagram to maintain its relevance and strengthen its brand image amid increasing competition in the beauty industry. This study aims to analyze how Viva Cosmetics constructs its brand identity through Instagram content using the Brand Identity Prism framework. The research employs a qualitative approach using content analysis by examining more than twenty posts from the official Instagram account of Viva Cosmetics. The analysis focuses on several dimensions of the Brand Identity Prism, including physique, culture, relationship, reflection, and self-image. The results indicate that the physique dimension is the most dominant element in Viva’s Instagram content, where product visuals, packaging, textures, shades, and functional benefits are prominently displayed. Additionally, the brand reinforces its local identity by presenting representations of Indonesian consumers and using simple, relatable communication styles. The relationship dimension is reflected through testimonials and interactive messages that emphasize consumer loyalty and long-term trust toward the brand. Meanwhile, the reflection and self-image dimensions portray consumers as women who practice simple self-care, value practicality, and maintain confidence in their appearance. These findings suggest that Viva Cosmetics strategically uses Instagram not only as a promotional platform but also as a medium to reinforce its identity as a legendary local brand that remains relevant across generations. The study highlights the importance of consistent brand identity representation and adaptive digital communication strategies in maintaining brand heritage and strengthening relationships with consumers in the digital environment.